Environment Sustainability Development Engineering Through The Reduction of Exhaust Gas Based on Metal Waste With Accurate Composition - Suheni, Suheni; Sunoko, Rudy; leksono, Amin Setyo; Wahyudi, Slamet (Jurnal Pembangunan dan Alam Lestari, 2026)
Technological developments have resulted in an increasing number of motorized vehicles such as motorbikes, cars, and other modes of transportation, which will result in a lot of air pollution due to exhaust emissions from fossil fuels. Substances from the hazardous exhaust gases include carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxides (NO or NOx), and hydrocarbons (HC). This research was conducted by designing a catalytic converter using a mixture of several metals obtained from various wastes in Small and Medium Enterprises. A mixture of copper, brass, aluminum, and zinc is to be made as a muffler or exhaust on the test vehicle, namely the 2005 Car with observed exhaust emissions, namely CO & HC, using a Gas Analyzer. Measurements were taken at vehicle rotation of 1000 rpm, 2000 rpm, 3000 rpm, 4000 rpm, and 5000 rpm. The results of this study indicate that the highest percentage reduction in CO levels was when using a catalyst with an engine speed of 2000 rpm, which was 5.23% with Pertamax fuel, while for Pertalite fuel, when using a catalyst with an engine speed of 2000 rpm, it was 5.5%. The highest percentage reduction in HC levels was when using a catalyst at 1000 rpm engine speed of 645 with Pertamax fuel, while for Pertalite fuel, using a catalyst at 1000 rpm engine speed was 705.5.   Keywords: Aluminium, Brass, Catalytic Converter, Copper, Gas Analyzer, Zinc